The Pearl Button (Journal of Parents and Teachers, 2016)
An educational proposal on the award-winning documentary, The Pearl Button, (Chile, 2015, 82') is developed. Its director, Patricio Guzman, tells how the ocean covers the entire history of the humanity. And how water welcomes the strength of the stars and transmits them to living beings. Water, the great divide of Chile, also keeps the secret of a mysterious button that was discovered in the seabed. The film is a tribute to the missing ones and shows that water also has voice and memory.Understanding related to the film are covered, also the film shows activities of experience, reflection and common action about respect, tolerance, forgiveness and peaceful coexistence.
Keywords: Educational proposal; documentary film; human rights; values and stories of lives; cinema and education.